Trend and Status of NPA of Selected Public and Private Sector Banks - Jyoti; Dr. Pooja Yadav (Innovative Research Thoughts, 2022)
In recent years, non-performing assets have become a global banking crisis. Same in India, the main worry for banks is non-performing assets. NPA is the most accurate measure of the banking industry's overall performance. The current research looks into the status of non-performing assets of a few different types of banks throughout the public and private sectors. For this study, secondary sources such as RBI papers, Statistical Tables pertaining to Banks in India, etc. are used to obtain data. The study finds that private and public sector banks exhibited an increasing trend in non-performing assets (NPA) before the Covid-19 pandemic, but NPA began to fall after the pandemic. The write-off of NPAs is a crucial contributor to this phenomenon.